2020
DOI: 10.4018/978-1-7998-1774-1.ch004
|View full text |Cite
|
Sign up to set email alerts
|

A Feminist Perspective Analysis of Gender in Cinema of Saudi Arabia

Abstract: In this study, Wadjda (2012), directed by Haifa El Mansur, will be analyzed from a feminist perspective in the context of the concept of gender. Mansur demonstrates to the cinema audience through a 10-year-old girl that women get out of their passive positions and get their rights partially. In this study, firstly the social structure of Saudi Arabia and the position of woman, the concept of gender and feminist film criticism, which is the analysis technique of the film, will be examined and the position of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…was produced (Sakr, 2008, p.400). Sarı (2020) suggested that, despite being produced by neighboring countries (including the UAE), this film used Saudi actors. In 2013, Wadjda was produced using Saudi actors including Waad Mohammed, and was classified as the first real Saudi film (La Caze, 2020;Harkins-Cross, 2014;Omar, 2021;Baughan, 2015).…”
Section: The Film Industry In Saudi Arabiamentioning
confidence: 99%
“…was produced (Sakr, 2008, p.400). Sarı (2020) suggested that, despite being produced by neighboring countries (including the UAE), this film used Saudi actors. In 2013, Wadjda was produced using Saudi actors including Waad Mohammed, and was classified as the first real Saudi film (La Caze, 2020;Harkins-Cross, 2014;Omar, 2021;Baughan, 2015).…”
Section: The Film Industry In Saudi Arabiamentioning
confidence: 99%
“…As opposed to political programs and governmental operations, films carry the capacity to initiate transformations leading to changes to one's worldview and understanding (Khan & Iqbal, 2020). Apart from immediate outcomes, films can induce a variety of changes to a person's life as the former to fulfill the following roles: broadening knowledge, sending meaningful messages, develop societal behaviors, and others (Sarı, 2020). The chosen perspective provides a basis for estimating the expected economic contributions of individual Saudis to the film industry in particular and the nation as a whole.…”
Section: Cultural Impactmentioning
confidence: 99%
“…Finally, the relative scarcity of data on Saudi Arabia's film industry can be explained by the 35-year-long hiatus, preventing Saudi nationals from producing, screening, and watching films on the big screen. Between 1983 and 2018, there are nearly no physical records or references that would be beneficial to the scholarly analysis of the topic (Sarı, 2020). From the economic perspective, the research of Saudi Arabia's film industry is almost entirely limited to the reports produced after the lifting of the cinema ban in April 2018 (Chulov, 2017).…”
Section: Introductionmentioning
confidence: 99%